An Adversity that Led to Achievement: Analyzing Dhruva's Rise from Humiliation - Sigdel, Ranjan (Haimaprabha, 2023)
This essay explores the story of Dhruva, a legendary prince in Hindu mythology, who overcame humiliation and achieved cosmic reign through his grit and unwavering devotion. This essay examines the story of the prince Dhruva not from Bhagavata Mahapurana but from a long poem by a contemporary Nepali poet Panthi. In this version the content, theme, language and styles are almost identical to its source tale i.e. Bhagavat Mahapurana. However, in many verses the gem of poetic genius of poet Panthi clearly shines through. The essay focuses on two key aspects of Dhruva's story: his humiliation by his step-mother, which prompted him to embark on a spiritual journey, and his attainment of cosmic reign, which symbolized his elevation to the highest level of spiritual realization. The essay analyzes the themes of adversity and perseverance that underpin Dhruva's story and shows how they offer valuable insights into how a feeling of humiliation could potentially lead one to achieving ultimate goal.